Regulatory Role of SIRT1 in Skeletal Muscle Hypertrophy: Molecular Implications - Dara Hanifa Rahman; Dedi Ardinata; Mutiara Indah Sari (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Background: Skeletal muscle hypertrophy is an adaptive process influenced by molecular signals and metabolic conditions. Sirtuin 1 (SIRT1), a NAD-dependent deacetylase, plays a crucial role in regulating skeletal muscle growth and regeneration through its interaction with key pathways such as mTOR, PGC-1?, FOXO, and myogenic factors. Aim: This literature review summarizes the current scientific evidence on the role of SIRT1 in muscle hypertrophy, including its effects on mitochondrial efficiency, oxidative stress reduction, and suppression of catabolic genes such as atrogin-1 and MuRF1. Method: A literature search was conducted using databases such as PubMed, ScienceDirect, and Google Scholar, focusing on articles from the last 10 years. Result: These findings indicate that SIRT1’s effects are highly context-dependent, varying with cellular energy status and external stimuli such as exercise or caloric restriction. Rather than directly inducing hypertrophy, SIRT1 facilitates a favorable cellular environment that enables sustained muscle growth. Conclusion: These insights offer promising potential for the development of molecular-based therapies to preserve or enhance muscle mass, particularly in aging populations or pathological conditions.